Public Transport Automatic Fare Collection Interoperability Assessing Options for Poland - World Bank (World Bank, Washington, DC, 2016)
In the second half of 2013, the World Bank secured grant funding from the Korea Green Growth Partnership for analytical support and technical assistance related to sustainable urban transport systems in select cities in Eastern Poland. Polish cities have followed international practice in introducing public transport smartcard ticketing that offers convenience to the passenger and savings to the operator through reduced fraud, shorter dwell times at stops, and less cash handling. Smartcards also offer more flexibility in setting and varying fares.However, one of the main benefits of smartcard ticketing internationally is in relation to integrating fares and ticketing across operators and modes.There is no overall direction as to what these automated fare collection (AFC) systems will provide, and there is limited levels of interoperability across the public transport networks and the rail network, which makes travelling across the country difficult. Going forward, Poland needs to consider the benefits that an integrated approach to public transport ticketing could deliver and agree a vision for delivering these benefits. This potential benefit has not been realized in Poland and little effort has been made to establish a common platform for ticketing, even within metropolitan areas.This Report focuses on options for introducing public transport automatic fare collection interoperability in Poland, building on the experience of other countries and taking into account recent changes in technology.Based on its review of the current situation in Poland and European experience with the introduction of AFC standards, the World Bank makes the following five recommendations: i) Establish a technical working group to develop a vision for AFC in Poland. ii) Support bank card, smartphone apps, and new technology developments and determine what is achievable over the medium-term in terms of interoperability. iii) Develop bank card specifications. iv) Do not develop a Polish AFC standard. v)Undertake a public transport fare review. Establishing a national smartcard standard and adopting it nationwide can be an expensive, complex, and lengthy process—as evidenced by the experience in the UK—and is not a ‘quick win’. Poland should consider innovative solutions enabled by new technologies and not aim to replicate approaches used in the UK or the Netherlands which were developed at a time when the technological options were different.